Asymmetric information as a barrier to knowledge spillovers in expert markets - Daniel Feser; Till Proeger (University of Göttingen, Center for European, Governance and Economic Development Research (cege), 2015)
This paper investigates barriers to effective knowledge spillovers for markets in which the product can be characterized as a credence good, i.e. its complexity impedes the evaluation of quality by customers both ex-ante and ex-post. We focus on the German market for energy efficiency consultants, as an emerging and subsidized sector in which the service offered has strong credence good properties. Based upon in-depth interviews with stakeholders, we analyze the determinants and barriers to knowledge spillovers. We find that the incentive to foster spillovers to increase suppliers knowledge is limited by the difficult commercialization of additional capabilities. The implementation of a public certification scheme has failed to increase the sectoral knowledge spillovers. By contrast, the participation in formal knowledge networks has been more effective in prompting companies to foster knowledge spillovers, which has also led to a higher degree of specialization. We conclude that access to certification schemes should be further restricted to increase market transparency and private networks should be supported to achieve the aim of increasing knowledge spillovers.
Keywords: D21; D82; H41; K23; L14; 330; credence goods; knowledge spillover theory of entrepreneurship; network